Lynchings, racial threat, and whites’ punitive views toward blacks - Stewart, Eric A. (Criminology, 2018)
Disparities in historical and contemporary punishment of Blacks have been well documented. Racial threat has been proffered as a theoretical explanation for this phenomenon. In an effort to understand the factors that influence punishment and racial divides in America, we draw on racial threat theory and prior scholarship to test three hypotheses. First, Black punitive sentiment among Whites will be greater among those who reside in areas where lynching was more common. Second, heightened Black punitive sentiment among Whites in areas with more pronounced legacies of lynching will be partially mediated by Whites’ perceptions of Blacks’ criminality and of Black‐on‐White violence in these areas. Third, the impact of lynching on Black punitive sentiment will be amplified by Whites’ perceptions of Blacks as criminals and as threatening more generally. We find partial support for these hypotheses. The results indicate that lynchings are associated with punitive sentiment toward Black offenders, and these relationships are partially mediated by perceptions of Blacks as criminals and as threats to Whites. In addition, the effects of lynchings on Black punitiveness are amplified among White respondents who view Blacks as a threat to Whites. These results highlight the salience of historical context for understanding contemporary views about punishment.